Tre racconti in Centopagine - Dario Pontuale (Flaubert: Revue Critique et Génétique)
This article shows the significant role held by Italo Calvino in Flaubertian interpretation and analyzes Flaubert’s influence on Calvino’s works, in particular Le Corbeau vient le dernier, Le Vicomte pourfendu, Le Baron perché. Focusing on the book of short stories Trois contes, published in 1980 by Calvino himself in the series “Centopagine”, that he himself created and directed, this study highlights not only the ascendance of Flaubert on Calvino, but also the analogies between Calvino’s texts and Flaubert’s book. We will also analyze the influence of Flaubert’s aesthetics in the genesis and structure of some of Calvino’s other works, such as Si par une nuit d’hiver un voyageur, Le Château des destins croisés and Les Villes invisibles.